Parcours d'Orient : recueil de textes offert à Christine Kepinski - Perello, Bérengère, (Archaeopress archaeology., 2016)
This volume contains 23 articles written by 26 authors in order to express the extent of their respect and friendship for Christine Kepinski. The topics addressed in their papers reflect the scientific work of Christine Kepinski, who always promoted interdisciplinary approaches and developed multi-scale analisis from the object itself to regional study.